Pendekatan Individual dalam Perkembangan Anak Didik - Sri Mulyati; Syamsiah Nur; Abd Syahid (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2021)
In the learning process, the teacher must be able to organize every learning activity and respect students as subjects who have talents and abilities. As a consequence of this, the learning process must also be developed through individual learning activities in order to obtain maximum learning outcomes. However, in the implementation there are still students who do not dare to ask the teacher when they find difficulties in doing assignments, there are students who have never been guided by the teacher in doing assignments, there are teachers who do not guide students in learning, there are students whose learning outcomes do not reach the KKM. even though they have received guidance from the teacher, and there are students whose learning outcomes reach the KKM even though they do not receive guidance from the teacher during the learning process. For this reason, the author intends to carry out research on the effect of the individual approach on student learning outcomes at the 018 Gemilang Jaya State Elementary School, Batang Tuaka District. The purpose of this study was to determine the implementation of the individual approach, student learning outcomes and the effect of individual approaches on student learning outcomes at the 018 Gemilang Jaya State Elementary School, Batang Tuaka District. This study uses a qualitative descriptive method. The instruments used are interviews, and observations.